REFLECTION OF ANKARA AS A STAGE OF NATIONAL STRUGGLE ON TURKISH NOVEL - Nurullah ULUTAŞ (Fırat University, 2019)
Taking stand from Ahmet Hamdi Tanpınar's description of “İstanbul” as “Out of the Stage", we can define Ankara as the heart of Anatolia and National Struggle. The National Struggle is a battle through which Turkish People were reborn from the ashes at the point of disapperance. The fact that it is also named as Independence War is an indicator for that. This war is undoubtedly the first struggle through which a nation stood up against Imperialists altogether. The literature of each nation bears the deep traces from Independence Struggle of that nation. Altough some intellectuals, primarily Ziya Gökalp, claim that Independence War is not treated in our literature enough, we can see that this struggle is used as the main theme or background in many novels, stories, poems and essays. We witness that some authors take stand from their own experiences and turn their observations into fiction in an autobiographic style in some of their works or they sometimes touch upon Independence War as a background without breaking the plotline of the novel or stody. In a process when the Ottoman Empire started to collapse in political, social and economic sense and to be shared as "Sick Man", this struggle which started from Samsun and was shaped in Sivas and Amasya headed towards a central state built in Ankara. This statization process reflects itself on our novels and stories with all stages. The center of the aids sent to İstanbul and all around the country was Ankara. The center of the army built by the voluntary patriots named Kuvay-ı Millî was Ankara. Based upon Yakup Kadri Karaosmanoğlu’s novel, Ankara, this paper will put emphasis on how Ankara showed an alteration in becoming of capital city, during and after the war of independence; what kind of charactreistics it undertook; and, how these elements were reflected in Turkish Novels.